2007
DOI: 10.1038/sj.bjp.0707473
|View full text |Cite
|
Sign up to set email alerts
|

Comparative potencies of 3,4‐methylenedioxymethamphetamine (MDMA) analogues as inhibitors of [3H]noradrenaline and [3H]5‐HT transport in mammalian cell lines

Abstract: Background and purpose: Illegal 'ecstasy' tablets frequently contain 3,4-methylenedioxymethamphetamine (MDMA)-like compounds of unknown pharmacological activity. Since monoamine transporters are one of the primary targets of MDMA action in the brain, a number of MDMA analogues have been tested for their ability to inhibit [ 3 H]noradrenaline uptake into rat PC12 cells expressing the noradrenaline transporter (NET) and [ 3 H]5-HT uptake into HEK293 cells stably transfected with the 5-HT transporter (SERT). Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 53 publications
3
24
0
3
Order By: Relevance
“…It is tempting to speculate that the lack of effect observed for N,N-dimethyl-MTA on the aortic contraction assay may be related to a decrease in the affinity of this drug for NET as compared with MTA, due to the presence of the tertiary amine function. Accordingly, it has been previously shown that N-substitution leads to a decrease in NET affinity for several different amphetamine derivatives [1,[41][42][43]. In this sense, data not shown in this study indicate that different substituents at the para position of the benzene ring in the MTA molecule do not affect aortic contraction, while the replacement of a hydrogen on the amino group of the MTA molecule by an allyl group decreases the potency in this assay.…”
Section: Discussionmentioning
confidence: 44%
“…It is tempting to speculate that the lack of effect observed for N,N-dimethyl-MTA on the aortic contraction assay may be related to a decrease in the affinity of this drug for NET as compared with MTA, due to the presence of the tertiary amine function. Accordingly, it has been previously shown that N-substitution leads to a decrease in NET affinity for several different amphetamine derivatives [1,[41][42][43]. In this sense, data not shown in this study indicate that different substituents at the para position of the benzene ring in the MTA molecule do not affect aortic contraction, while the replacement of a hydrogen on the amino group of the MTA molecule by an allyl group decreases the potency in this assay.…”
Section: Discussionmentioning
confidence: 44%
“…MDMA is known to inhibit the DA transporter (DAT), NE transporter (NET), and 5-HT transporter (5-HTT) [25][26][27].…”
Section: Inhibition Of Dat Net and 5-htt By Mdmamentioning
confidence: 99%
“…However, adopting the approach of pharmacological transporter blockade in this work, neither MDMA nor two of its more potent redesigned analogues were seen to be delivering their toxic hit to lymphoma cells via any of the three monoamine transporters probed. Moreover, Montgomery and colleagues [34] examining the action of MDMA and several MDMA analogues on 5-HT and NA uptake in cells transfected with SERT or NET reported a Hill coefficient for inhibition by MBDB (our compound 3) of~1 for both HEK-SERT and PC12-NET compared to that generated from its anti-lymphoma action in this study of >3. Others have shown that MDMA is capable of promoting cell death independently of SERT expression or activity [35].…”
Section: Discussionmentioning
confidence: 48%